2015
DOI: 10.1002/eat.22454
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders in military and veteran men and women: A systematic review

Abstract: The high rates of EDs among military and veteran samples underscore the importance of further research, as well as the importance of screening and intervention efforts, in these understudied populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 69 publications
3
76
1
1
Order By: Relevance
“…At least one study suggests that men veterans are more likely to report disordered eating than women veterans (Higgins et al, 2013) and men may have different treatment preferences (Robertson et al, 2015). Further, there is reason to believe that stigma and the perception of disordered eating as a “women’s” problem could lead men to underreport disordered eating (Bartlett & Mitchell, 2015), suggesting that disordered eating among men may be a larger public health concern than currently understood.…”
Section: Future Workmentioning
confidence: 99%
See 2 more Smart Citations
“…At least one study suggests that men veterans are more likely to report disordered eating than women veterans (Higgins et al, 2013) and men may have different treatment preferences (Robertson et al, 2015). Further, there is reason to believe that stigma and the perception of disordered eating as a “women’s” problem could lead men to underreport disordered eating (Bartlett & Mitchell, 2015), suggesting that disordered eating among men may be a larger public health concern than currently understood.…”
Section: Future Workmentioning
confidence: 99%
“…Treating disordered eating is of special importance to veterans served by the Veterans Health Administration (VA). A recent systematic review found prevalence estimates of disordered eating among veteran and military men and women to be comparable to or higher than prevalence estimates for the general population (Bartlett & Mitchell, 2015). At the extreme end of the spectrum, one included study found that almost 80% of the thousands of participants in VA’s weight loss program report disordered eating (Higgins et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Необходимо це ленаправленное медицинское обследование военнослужащихженщин по раннему выяв лению признаков болезней указанных классов [27]. Некоторые практические рекомендации с целью массаконтролируемого ведения бе Рис.…”
Section: таблицаunclassified
“…Similarly, mortality risk increased by nearly 60% when individuals were faced with weight discrimination, and this increase was not better explained by other psychological or physical risk factors (Sutin et al, 2015). Military service members may be at increased risk for experiencing weight stigma due to unfavorable consequences for not meeting weight requirements (i.e., remedial fitness programs, discharge; Bartlett & Mitchell, 2015; Stewart et al, 2011). Due to the incidence of mental health stigma in military culture, veterans with PTSD may experience prejudice and decreased social support (Pietrzak et al, 2009), both of which can increase suicidal ideation and attempts (DeBeer et al, 2014; Fergusson et al, 1999; Perry et al, 2012).…”
Section: Introductionmentioning
confidence: 99%